Accumulation of homoplasmic mtDNA point mutations in erythroblasts isolated from the bone marrow of patients with refractory anemia with ring sideroblasts (RARS) - Babušiaková, E; Vyoral, Daniel; Neuwirtová, Radana; Šišková, Magda; Zeman, Jiří; Kmoch, Stanislav (Mitochondrion, 2004)
It was hypothesised that mitochondrial iron overload in patients with refractory anemia with ring sideroblasts (RARS) results from mitochondrial DNA (mtDNA) mutations. To analyse the mtDNA sequence of iron storing mitochondria sensitively, we developed new protocols for selective erythroblasts isolation, mtDNA PCR amplification and sequencing. Using this approach, we found in each of the three RARS patients examined a unique spectrum of homoplasmic mtDNA point mutations affecting several mtDNA genes. Prediction analyses suggest that identified mutations do not result in major perturbations of mitochondrial functions and are tolerated. We discuss a mechanism explaining how the mutations identified may contribute to RARS pathogenesis.
Keywords: mutace; ženské pohlaví; sideroblastická anemie; lidé středního věku; lidé; Female; senioři; Mutation; Aged; Anemia, Refractory; Middle Aged; DNA, Mitochondrial; mitochondriální DNA; refrakterní anemie; Anemia, Sideroblastic; Humans